PERIZINAN DI BIDANG PERBANKAN YANG BERIMPLIKASI TINDAK PIDANA - Nooritza Meidahnia (Yuridika, 2014)
In order to support the improvement of the implementation of development in Indonesia, banking institutions experienced fluctuating growth along with the progress and political developments in Indonesia, the development of the international economy also in line with increased demand banking services needs of the community will be strong and feasible. This is then gives a very strategic role in the development of the banking institutions in Indonesia because of the bank as a means to harmonize and balance of each element of the trilogy of development, economic growth and national stability, as defined in Article 4 of Law No. 10 of 1998 on Banking.Keywords: license, banking, abuse.